On the Existence of Robot Zombies and our Ethical Obligations to AI Systems - Luke R. Hansen (Journal of Social Computing, 2023)
As artificial intelligence algorithms improve, we will interact with programs that seem increasingly human. We may never know if these algorithms are sentient, yet this quality is crucial to ethical considerations regarding their moral status. We will likely have to make important decisions without a full understanding of the relevant issues and facts. Given this ignorance, we ought to take seriously the prospect that some systems are sentient. It would be a moral catastrophe if we were to treat them as if they were not sentient, but, in reality they are.